Antibody‐based cell‐surface proteome profiling of metastatic breast cancer primary explants and cell lines. Issue 4 (2nd March 2018) - Donnenberg, Vera S.; Zhang, Jayce Jieming; Moravcikova, Erika; Meyer, Ernest Michael; Lu, Haihui; Carson, Christian T.; Donnenberg, Albert D.
Abstract: Flow cytometric cell surface proteomics provides a new and powerful tool to determine changes accompanying neoplastic transformation and invasion, providing clues to essential interactions with the microenvironment as well as leads for potential therapeutic targets. One of the most important advantages of flow cytometric cell surface proteomics is that it can be performed on living cells that can be sorted for further characterization and functional studies. Here, we document the surface proteome of clonogenic metastatic breast cancer (MBrCa) explants, which was strikingly similar to that of normal mesenchymal stromal cells ( P  = 0.017, associated with Pearson correlation coefficient) and transformed mammary epithelial cells ( P  = 0.022). Markers specifically upregulated on MBrCa included CD200 (Ox2), CD51/CD61 (Integrin α5/β3), CD26 (dipeptidyl peptidase‐4), CD165 (c‐Cbl), and CD54 (ICAM‐1). Proteins progressively upregulated in a model of neoplastic transformation and invasion included CD26, CD63 (LAMP3), CD105 (Endoglin), CD107a (LAMP1), CD108 (Semaphorin 7A), CD109 (Integrin β4), CD151 (Raph blood group), and disialoganglioside G2. The proteome of the commonly used cell lines MDA‐MB‐231, MCF7, and BT‐474 were uncorrelated with that of MBrCa ( P  = 1.0, 1.0, 0.9, respectively). The comparison has demonstrated the mesenchymal nature of clonogenic cells isolated by short‐term culture of metastatic breast cancer, provided several leads for biomarkers and potential targets for anti‐invasive therapy, including CD200, and highlighted the limitations of breast cancer cell lines for representing the cell surface biology of breast cancer. © 2017 International Society for Advancement of Cytometry